Estudio fenométrico e indice de balance hídrico del cultivo de arroz oryza sativa l en el cantón Arenillas - Espinoza Malla, Kleber Stalin (2015)
The work entitled "STUDY FENOMÉTRICO WATER BALANCE AND INDEX OF RICE (Oryza sativa L.) IN THE CANTON ARENILLAS", the overall objective raised the "Determining the fenometría and rate of water balance of rice (Oryza sativa L.) under flood irrigation to raise achievement in the district of Arenillas, Province of El Oro " for which specific objectives were considered the agricultural fenometría Determine rice cultivation under irrigation by flooding, determine the crop coefficient and water use plants and Perform financial analysis of different treatments, and performed at the Experimental Farm "The Cuca" the canton Arenillas under the responsibility of the Provincial Autonomous Government of El Oro, for evaluating the following variables: height of seedlings at the time of transplantation, root length transplant day, number of tillers at 30 and 60 days after sowing, plant height at flowering, percentage of productive tillers per hill children productive, Number productive panicles, number of grains per panicle, panicle length, phenology, Performance, Profitability of treatments. The research was developed with a Design Randomized Complete Blocks (DCBA) in which there were two varieties as treatments and four replicates, the tabulation of data was performed with the help of Software Statgraphic Plus, with a level of 95 % and comparison Test classes Fisher (LSD) was used with a confidence level of 95%. The SFL09 variety on the INIAP 15 production levels allowing increased profitability and Benefit - Cost Ratio was highlighted. Also managed to establish the necessary water requirements of rice.